Phytochemical, Nutritional and Medicinal Profile of Cucumis sativus L. (Cucumber) - Javid, Hina; Fatima, Urooj; Rukhsar, Aqsa; Hussain, Shabbir; Bibi, Shagufta; Bodlah, Muhammad Adnan; Shahzad, Hafiza Hadiya; Dilshad, Muhammad; Waqas, Muhammad; Sharif, Ayesha (Food Science and Engineering, 2024)
Current studies were performed to review the phytochemistry, nutritional benefits, medicinal/therapeutic value, and cosmetic importance of cucumber (Cucumis sativus L.). Cucumber fruits are an important part of the human diet, often used in salads, pickles, and sauces, due to their nutritious qualities and health benefits. They are a good source of vitamins, minerals, soluble carbohydrates, proteins, etc. The leaves, flowers, seeds, fruits, and bark of cucumber are rich in various phytoconstituents, including phenols, glycosides, alkaloids, flavonoids, carotenoids, tannins, steroids, terpenoids, phytosterols, phytoestrogens, saponins, minerals, proteins, carbohydrates, resins, and vitamins. Cucumbers are traditionally used to treat a variety of diseases, including high blood pressure, blood sugar issues, cancer, high cholesterol, kidney stones, constipation, Alzheimer’s disease, eczema, hypertension, atherosclerosis, and diabetes-related problems. The therapeutic/pharmaceutical value of cucumbers may be attributed to their laxative, antioxidant, anti-diabetic, analgesic, anti-hepatotoxic, anti-diarrheal, anti-fungal, anti-bacterial, thrombolytic, anti-ulcer, anti-inflammatory, cytotoxic, free radical scavenging, and wound-healing properties. Cucumbers also improve skin quality, promote skin whitening and smoothness, enhance natural beauty, regulate hydration, aid in weight loss, and reduce fat. They are used in cucumber creams, perfumes, face packs, and facials. Cucumber extract is incorporated into several formulations for topical skin treatments. This review article aims to explore the traditional uses, phytochemical contents, nutritional value, cosmetic applications, and pharmacological and therapeutic potential of cucumbers. It will be highly beneficial for a wide range of readers, including the general public, researchers, physicians, farmers, and agricultural stakeholders.